Bio-efficacy of imidazolinones in weed control in a tropical paddy soil amended with optimized agrowaste-derived biochars - Yavari, S. (Elsevier Ltd, 2022)
Biochar is a black carbon sorbent that has the ability to stabilize organic substances in soil and, therefore, the potential to reduce their bio-availability. This sustainable material can be produced from locally-available agro wastes. The present study, for the first time, investigated the effects of biochars produced from oil palm empty fruit bunches (EFB) and rice husk (RH) on the efficiency of imazapic and imazapyr (two polar members of imidazolinone herbicides) as well as OndutyÂ®, a mixture of them. It was executed in a Malaysian paddy field soil during a 30-day greenhouse experiment. The presence of optimized EFB and RH biochars in the heavy soil generally increases weed seeds germination and plants growth due to stabilization of the herbicides. The effect of EFB biochar was found higher than RH biochar having a higher affinity to the herbicides. An increase in the biochars application rates enhanced their effects as a soil modifier. Differences were more significant in the higher herbicides doses. Efficacies of all the herbicides were generally decreased in the biochar-amended soils. In the presence of 0.5 biochar in soil, the GR50 values for all herbicides were almost similar to biochar-free soil. In a 1.0 biochar-soil mixture, GR50 values of the herbicides increased by about 1.5 times. Bio-efficacies of the herbicides decreased by around 2.0 times as the biochar application rate enhanced to 2.0. The greatest GR50 values were obtained in the presence of 4.0 biochar in the soils and were about 7.0â8.5 folds, indicating the high capability of amended soil in the stabilization of the herbicides. The findings of this study can help to reduce imidazolinonesâ pollution and, in this way, prevent the threats of their residues to the environment. Â© 2022 Elsevier Ltd